Student experience of school science - Shirazi, Shaista (International journal of science education, 2017)
This paper presents the findings of a two-phase mixed methods research study that explores the link between experiences of school science of post-16 students and their decisions to take up science for their higher studies. In the first phase, students aged 16-17 (n = 569) reflected on the past five years of their school science experience in a quasi-longitudinal approach to determine a typology of experiences. The second phase entailed data collection through interviews of a sample of these students (n = 55) to help triangulate and extend findings from the first phase. Students taking up science post-16 reported significantly more positive experiences of school science than students who had decided not to take science further. Of school-related factors influencing experiences of school science curriculum content was the most important followed by being interested and motivated in the subject. There is evidence that interest and motivation in science depend on teacher practice and the perception of science as a difficult subject.